2019
DOI: 10.18699/vj19.517
|View full text |Cite
|
Sign up to set email alerts
|

The role of olfactory transport in the penetration of manganese oxide nanoparticles from blood into the brain

Abstract: There is no doubt that various nanoparticles (NPs) can enter the brain from the nasal cavity. It is assumed that NPs can penetrate from blood into the central nervous system (CNS) only by breaking the blood–brain barrier (BBB). The accumulation of NPs in CNS can provoke many neurological diseases; therefore, the understanding of its mechanisms is of both academic and practical interest. Although hitting from the surface of the lungs into the bloodstream, NPs can accumulate in various mucous membranes, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Позитивно заряджені частинки потрапляють у клітини легше, ніж негативно заряджені. Встановлено передислокацію НЧ по нюхових, трійчастих, трахеобронхіальних нервах і нейром'язових з'єднаннях [12]. Експериментально підтверджено проникнення НЧ між клітинами, механічне пошкодження мембран клітини, а також фагоцитоз НЧ клітинами з подальшим переміщенням їх у зовнішнє середовище [13,14].…”
Section: результати дослідження та їх обговоренняunclassified
“…Позитивно заряджені частинки потрапляють у клітини легше, ніж негативно заряджені. Встановлено передислокацію НЧ по нюхових, трійчастих, трахеобронхіальних нервах і нейром'язових з'єднаннях [12]. Експериментально підтверджено проникнення НЧ між клітинами, механічне пошкодження мембран клітини, а також фагоцитоз НЧ клітинами з подальшим переміщенням їх у зовнішнє середовище [13,14].…”
Section: результати дослідження та їх обговоренняunclassified
“…
Motivation and Aim: In recent years, air pollution has increased significantly, and humans, like other terrestrial animals, are constantly exposed to solid aerosols, which may contain various xenobiotics, including nanoparticles (NPs) that can enter the brain from the nasal cavity [1]. Moreover, it was shown that the addition of nanoparticles to the cellular environment induces the formation of stress granules (SG), which are the cellular response to stress [2].
…”
mentioning
confidence: 99%
“…Therefore a noninvasive method to assess axonal transport rate could potentially allow for early diagnosis of such diseases. Earlier it was shown that Mn3O4 nanoparticles (Mn3O4-NP) can act as an magnetic resonance imaging (MRI) contrast, that upon intranasal injection can be engulfed by olfactory neurons, and subsequently get transported into the deeper brain areas [3]. In this study we have assessed Mn3O4-NP spreading in brain of two congenic mice strains: C57Bl and B6.Cg-Tg(Prnp-SNCA*A53T)23Mkle (with high α-synucleinopathy risk, motor impairments become evident at the age of 12 months [4]).…”
mentioning
confidence: 99%
“…Each group consisted of 6 males. Mn3O4-NP were prepared as previously described [3]. They were suspended in saline and intranasally instilled.…”
mentioning
confidence: 99%